The contents of the opening article of electronic newspaper (Al-Nabaa): (Analytical study of duration 2015 for 2018) - Dari, Khudher Abbas (ALBAHITH ALALAMI, 2020)
The study aimed to identify what (isis) (Daesh) have been touched in the opening article of Al-Nabaa newspaper This objective is organized for asset of sub-targets it is the knowledge of media discourse and for those who are directed and methods of employing the strong content debt organization and we used the survay method to monitor and understand the content of opening anticale and the researcher took the numbers of the newspaper for years 2015-2018 consist of 157 The results of this study are : * Use religious texts from (Holly qoran) (Abbreission of the prophetic) Remove from its context and empby them in justifying in what use of violence. * The terrioist organization depicts that conflict between Muslims crusaders and the collaborators with them. * The organization demands to have military and security operations in order to weak the levels of security forces. * Use the long – term war to drain the capabilities of military and government both physically and humanly . * After victory the organization is required to be unfairly confirmed the military farces but also the proposals for peripherals and terrorism . * The Relation of the terrorism organization is negative with everyone.